Strategic Behavioral Adaptations in Sports Management: A Game Theoretical Analysis of Sustainable Practices in China - Qiang Zhang; Weigong Du; Yuxing Chen; Yanmin Man; Xingyu Xue, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The adoption of sustainable practices, such as the use of organic methods, is increasingly relevant in sports management as it parallels initiatives in the agricultural sector aimed at carbon sequestration. This paper explores the dynamics of decision-making in sports facilities management through the lens of an evolutionary game model that assesses the interactions between sports organizations (akin to farmers) and regulatory bodies (similar to local governments) in China. The model investigates how these entities navigate conflicts and cooperative strategies regarding the adoption of sustainable practices. Simulation tools validate the game model, providing insights into the strategic choices influenced by various parameters. Sensitivity analysis reveals that: (1) subsidies alone may not effectively promote the adoption of sustainable practices; (2) the likelihood of adopting sustainable measures increases with the costs associated with traditional practices, potential benefits to the organization, political gains for regulatory bodies, and penalties for non-compliance; (3) significant improvements in regulatory performance, reduced administrative costs, enhanced policy support, and lowered implementation costs are crucial for encouraging sustainability in sports management. These findings suggest a framework for sports organizations to enhance their strategic and behavioral approaches to sustainability, fostering better environmental and organizational outcomes.